A 5-year-old boy with acute neurological disorder from anteflexion-induced cervical cord compression after tracheal surgery: Radiological findings similar to Hirayama disease. (January 2021) - Sekioka, Akinori; Fukumoto, Koji; Kawasaki, Tatsuya; Koyama, Masashi; Fujimoto, Yoh; Miyake, Hiromu; Nomura, Akiyoshi; Yamada, Susumu; Kanai, Risa; Makino, Akihiro; Urushihara, Naoto
Abstract: Constant neck flexion has been considered crucial to reducing anastomotic tension after tracheal resection. However, in rare cases, anteflexion can cause cervical cord damage, leading to acute neurological disorders such as tetraplegia. Here, we report a case of 5-year-old boy presenting with acute neurological disorder triggered by a chin-to-chest position over 4 days of deep sedation after cricotracheal resection. The radiological findings would suggest a mechanism similar to Hirayama disease, in which a shift of the dura leads to chronic muscular weakness and atrophy in young populations.